1998
DOI: 10.1074/jbc.273.50.33817
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Is Essential for Estrogen Receptor Interaction with Its Motif and Activation of Responsive Promoter

Abstract: Calmodulin (CaM) has been reported to have affinity for the estrogen receptor (ER). Observations reported here reveal a direct physical interaction between purified CaM and ER. This direct ER-CaM interaction may be an initial event preceding the assembly of ER plus auxiliary proteins into the active ER complex with its DNA motif, the estrogen response element. We demonstrate that CaM is an integral component of this complex by using a system reconstituted from purified ER and nuclear extract from ER-negative b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 40 publications
(16 reference statements)
2
50
0
Order By: Relevance
“…the initial step of the transcription cycle. In contrast to CaM inhibitors which have been reported to impede ER-mediated transactivation (Biswas et al, 1998;Garcia Pedrero et al, 2002;Li et al, 2005), synthetic peptides containing the P295 -T311 sequence would confer to ER an activated conformation similar to that induced by CaM, even if they are unable to directly interact with CaM.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…the initial step of the transcription cycle. In contrast to CaM inhibitors which have been reported to impede ER-mediated transactivation (Biswas et al, 1998;Garcia Pedrero et al, 2002;Li et al, 2005), synthetic peptides containing the P295 -T311 sequence would confer to ER an activated conformation similar to that induced by CaM, even if they are unable to directly interact with CaM.…”
Section: Discussionmentioning
confidence: 97%
“…This elimination process facilitates the access of newly govern transcription and turnover rate of ER are closely interrelated Metivier et al, 2003;Yan et al, 2003;Laios et al, 2005). Unexpectedly CaM, while being an important determinant of ER-mediated transcription (Biswas et al, 1998;Garcia Pedrero et al, 2002;Li et al, 2003;Li et al, 2005) has been reported to protect ER against proteasomal degradation (Castoria et al, 1988;Li et al, 2001;Li et al, 2006). This paradox led us to explore further the mechanism of action of this co-regulator.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies from our laboratory revealed that CaM increases the ability of the receptor to associate with estrogen response elements (EREs) (Bouhoute, Leclercq, 1995). Subsequent independent investigations (Biswas et al, 1998) indicated that it operates as a co-regulator of major importance for the formation of stable ERα~ERE complexes. The additional observations of these authors that a CaM antagonist (W7) abrogates the transactivation of an E 2 -responsive promoter led them to conclude that CaM participates to ERα-mediated transcription.…”
Section: Historical Backgroundmentioning
confidence: 99%